An Analysis Mathematics Learning Quality of Primary School Students Using Thematic Approach - Ika Prasetyani; Sumargiyani Sumargiyani (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2018)
This study aims to analyze the mathematics learning quality of primary school students using a thematic approach. This research subject was primary school student one grade of SD Negeri 4 Sidorekso, Kudus. This study type was classroom action research that involves 30 students. The method used descriptive qualitative. The data collected by diagnostic test techniques, observation and interview sheets. The analysis showed an improvement in mathematics learning. It can be seen in the first cycle increased from 63% in the first meeting to 69% at the second meeting. The second cycle from 84% to 87% and the third cycle from 96% to 97%. Moreover, student achievement increased. In the first cycle, the average score was 76 and 70% for classical. In the second cycle, the average was 84 and 82% for classical. In the third cycle, the average was 91 and 100% for classical. The positive response from the students and teachers use the thematic approach process can be seen from the result of an interview that the thematic approach can improve the interest and motivation of the students.